A Double-Cladding Single Polarization Photonic Crystal Fiber and Its Structure Deviation Tolerance - Yating Shen; Longfei Wang; Meisong Liao; Yinyao Liu; Fei Yu; Dakun Wu; Wanjun Bi; Yongzheng Fang; Weiqing Gao (IEEE Photonics Journal)
We propose a novel broadband single-polarization single-mode (SPSM) photonic crystal fiber with hexagonally latticed circular airholes. Combined with our fabricated polarization maintaining fiber, it has demonstrated that the enlarged air holes in the outmost layer are superior for the confinement loss reduction. At the optimized parameters, the wavelength of SPSM region ranges from 1.52 to 2.13 $μ$ m, where only y-polarized fundamental mode exists and the confinement loss is 0.051 dB/km at 1.55 $μ$ m. The influence of realistic fabrication errors involving structure deviation on SPSM operation has also been systematically investigated.